Moderasi Beragama Dalam Perspektif Sa’id Hawwa’ Dan Implementasinya Terhadap Nilai Humanisme (Kajian Kitab al-Asas Fi al-Tafsir) - Juniarti, Yevi; Shohib, Muhammad (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2024)
Religious moderation means practicing religion by choosing the middle path, in the sense of not being radical, not extreme, not rigid, and not excessive in dealing with differences in groups that are not the same as ourselves. It also means not being overly excessive in practicing religious teachings to the point of neglecting the surrounding world and disregarding others. Respecting fellow human beings is also embodied in Pancasila, which states